Faktor-Faktor Yang Mempengaruhi Sustainable Report Pada Perusahaan Pertambangan - Retnoningsih, Sri; Wijayanti, Sukma; Risnawati, Heni (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
The Sustainable Development Goals (TPBs/SDGs) are sustainable development agreements based on human rights and equality. TPB/SDGs have Universal, Integration and Inclusive principles, to ensure that no one is left behind or is called No One Left Behind. Disclosure of financial reports is support from economic entities in achieving SDGs goals. Sustainability reports are one of the media as a means of communicating an entity's responsibility towards economic, social and environmental aspects. This research aims to analyze what factors influence the quality of disclosure in sustainability reports in order to support the SDGs agenda. The data used are annual financial reports and sustainability reports which have been published through the Indonesia Stock Exchange for the 2021-2022 period in Mining and Energy Companies. The research results show that Leverage has no effect on the sustainable report, female directors have no effect on the sustainable report and company size has an effect on the sustainable report. From the model test results, an R Square value of 0.628% was obtained. This research model is quite good because it is able to test more than 50%, while 37.25 is a variable outside this research